Anterior cingulate cortex involved in social food‐foraging decision‐making strategies of rats. Issue 10 (8th September 2017) - Zhong, Xiaolin; Deng, Sihao; Ma, Wenbo; Yang, Yuchen; Lu, Dahua; Cheng, Na; Chen, Dan; Wang, Hui; Zhang, Jianyi; Li, Fang; Li, Changqi; Huang, Hua‐Lin; et al.
Abstract: Introduction: Decision making as a complex cognitive process involves assessing risk, reward, and costs. Typically, it has been studied in nonsocial contexts. We have developed a novel laboratory model used with rodents to detect food‐foraging decision‐making strategies in different social settings. However, the brain regions that mediate these behaviors are not well identified. Substantial evidence shows that the anterior cingulate cortex (ACC) participates in evaluation of social information and in decision making. Methods: In this study, we investigated the effect of bilateral lesions in the ACC on established behaviors. Kainic acid (KA) was administered bilaterally to induce ACC lesions, and saline microinjection into the ACC was used in the sham group. Results: In contrast to the sham‐lesioned animals, when faced with the choice of foraging under a social context, rats with ACC lesions preferred foraging for the less desirable food. Moreover, in these situations, the total amount of food foraged by the ACC‐lesioned group was less than the amount foraged by the sham group. Notably, neither social interactions nor social agonistic behaviors were affected by ACC lesions. Conclusions: These data suggest that the ACC is a key region underlying neural processing of social decision‐making, specifically tending to compete for foraging high predictive reward food. Abstract : Our research in novel laboratory model used with rodents found that the anterior cingulate cortex (ACC) is a key region underlying neural processing of social decision‐making. When faced with the choice of foraging under a social context, rats with ACC lesions preferred foraging for the less desirable food. Notably, neither social interactions nor social agonistic behaviors were affected by ACC lesions.